World economic slowdown - Günter Großer; Günter Weinert (Intereconomics, 1991)
In the course of last year, the economic climate cooled down world-wide; it was placed under additional strain in late summer by the Gulf crisis. In some industrialized countries, especially the USA, recessive trends have recently gained prevalence. Do indications for 1991 therefore point to a downturn in the world economy?
Keywords: 330; Economic Trends